Effectiveness of Antioxidant Compounds in Minaserua Herbal Drink from Bima as a Functional Food on Blood Pressure and Cholesterol Levels - Anisah Anisah; Baiq Dewi Sukma Septiani (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Hypertension and hypercholesterolemia are major risk factors for degenerative diseases with increasing prevalence. Minaserua, a traditional herbal drink from Bima made from black glutinous rice, ginger, turmeric, clove, Javanese chili, black pepper, palm sugar, and coconut milk, is rich in bioactive compounds and potentially reduces blood pressure and cholesterol levels. This study employed a pre-post control group design. Participants were divided into an experimental group, receiving Minaserua daily for 2–4 weeks, and a control group, receiving no intervention. Blood pressure and cholesterol levels were measured before and after the intervention. Antioxidant activity was analyzed using the DPPH spectrophotometric method. Statistical analysis was performed using paired t-tests and independent t-tests. Minaserua exhibited strong antioxidant activity with an IC-50 of 41.30 mg/ml. The experimental group showed significant reductions in total cholesterol, LDL, triglycerides, and significant increases in HDL (p < 0.05), along with significant decreases in systolic and diastolic blood pressure (p < 0.05). The control group showed no significant changes, except for a marginal increase in HDL. Minaserua herbal drink effectively improves lipid profiles and lowers blood pressure, supporting its potential as a functional food for preventing hypertension and hypercholesterolemia.